Urgensi Wawasan Kebangsaan dalam Penguatan Persatuan dan Kesatuan di Era Digital: Wawasan Kebangsaan dalam Perspektif Keberagaman - Maimun Maimun; Badrus Sholeh; Melkya Khailana Tantri (Institut Nurul Islam Mojokerto, 2025)
This research was conducted with the aim of answering all problems regarding the meaning of national insight, the reasons for how important it is to have national insight in diversity in the digital era, as well as the positive and negative impacts of Indonesia's diversity, which is none other than to create the embodiment of national insight, namely to maintain unity in diversity and multicultural education to strengthen Bhineka Tunggal Ika. Although conflict has been a matter of great concern until now, it has not become a great fear that can reduce the spirit of society, but this is a challenge and fuel for the struggle to show that diversity can be beautiful with the spirit of unity